A ontologia plural da política no pensamento de Antonio Negri - Fiedler, Cássia Zimmermann (2022)
The presente dissertation, carried out in the Postgraduate Program in Philosophy at PUCRS, specifically, in the Area of Concentration called Ethics and Political Philosophy integrated to the Research Line designated as State and Theories of Justice, aimed to presente, through critical analysis and bibliographic surveys, the plural ontology of politics externalized by Antonio Negri. To this end, the four main concepts developed by the author in recent years were exposed, delimited and intertwined, as well as their intertones, namely the Empire, the multitude, the common and the assembly, which are correspondingly divided into the three different chapters that make up this work. On this threshold, it is within the existing dynamic between biopolitics and biopower, which interconnects the Empire and the multitude, that the first investigations of this research were carried out. After signaling the brand new inclination that translates a different political and social order, which contemplates the absolute in its spectrum of influence, the objective was to clarify the monstrous alternative that confronts the imperial powers: the multitude, which is structured by the interaction between the mode common production and its respective fruits. Finally, the assembly and its plural dynamics were highlighted, indicating, in the last instance, the constitution processes related to the spectrum of common productivity, being illuminated in this way the substrates for the realization of resistances that take place at broader social levels.